Global Lipschitz stability for a fractional inverse transport problem by Carleman estimates. Issue 4 (12th March 2021) - Kawamoto, Atsushi; Machida, Manabu
Abstract : We consider a fractional radiative transport equation, where the time derivative is of half order in the Caputo sense. By establishing Carleman estimates, we prove the global Lipschitz stability in determining the coefficients of the one-dimensional time-fractional radiative transport equation of half-order.